Inertial Sensors are a Valid Tool to Detect and Consistently Quantify Jumping - Spangler, Rhys; Rantalainen, Timo; Gastin, Paul B.; Wundersitz, Daniel (International Journal of Sports Medicine, 2018)
Considering the large and repetitive loads associated with jumping in team sports, automatic detection and quantification of jumping may show promise in reducing injury risks. The aim of this study was to validate commercially available inertial-movement analysis software to detect and quantify jumping in team sports. In addition, the test-retest reliability of the software to quantify jumping was assessed. Seventy-six healthy male participants completed a team sport circuit six times containing seven common movements (including three countermovement and two single-leg jumps) whilst wearing an inertial sensor (Catapult Sports, Australia). Jump detection accuracy was assessed by comparing the known number of jumps to the number recorded by the inertial movement analysis software. A further 27 participants separately performed countermovement and single-leg jumps at 33%, 66% and 100% of maximal jump height over two sessions. Jump height quantification accuracy was assessed by comparing criterion three-dimensional motion analysis-derived heights to that recorded by the inertial movement analysis software. Test-retest reliability was assessed by comparing recorded jump heights between both testing sessions. Catapult’s inertial movement analysis software displayed excellent jump detection accuracy (96.9%) and test-retest jump height quantification reliability (ICC: 0.86 [countermovement jump], 0.88 [single-leg jump]). However, significant mean bias (–2.74 cm [95% LoA –10.44 – 4.96]) was observed for jump height quantification. Overall, Catapult’s inertial movement analysis software appears to be a suitable method of automatically detecting jumping in team sports, and although reliable, caution is advised when using the IMA software to quantify jump height.
Keywords: accelerometer; gyroscope; reliability; sensitivity; jump detection; activity detection